2017
DOI: 10.1186/s12913-017-2566-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaption, implementation and evaluation of collaborative service improvements in the testing and result communication process in primary care from patient and staff perspectives: a qualitative study

Abstract: BackgroundIncreasing numbers of blood tests are being ordered in primary care settings and the swift and accurate communication of test results is central to providing high quality care. The process of testing and result communication is complex and reliant on the coordinated actions of care providers, external groups in laboratory and hospital settings, and patients. This fragmentation leaves it vulnerable to error and the need to improve an apparently fallible system is apparent. However, primary care is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…26 A service co-design project sought to address these weaknesses and, although able to make some changes that were well received by patients and staff, time and resource constraints limited its impact. 27 Ensuring that a robust and fit-forpurpose system is in place is vital given the increasing number of test results handled in primary care. 28 Implications for research and practice Study participants' views on which of the guidelines are helpful, their current implementation status, and suggested facilitators for further implementation (Box 2), together, help to prioritise future research in this area.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…26 A service co-design project sought to address these weaknesses and, although able to make some changes that were well received by patients and staff, time and resource constraints limited its impact. 27 Ensuring that a robust and fit-forpurpose system is in place is vital given the increasing number of test results handled in primary care. 28 Implications for research and practice Study participants' views on which of the guidelines are helpful, their current implementation status, and suggested facilitators for further implementation (Box 2), together, help to prioritise future research in this area.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The male psychiatric clothes included t-shirts and trousers (1), medical white coats (2), suits (3), as well as shirts and trousers (4). Female psychiatrist's cloths included (1) colored mantos and scarves (1), black headdresses and white medical coats (2), black veils (3), and black head dresses and mantos (4). The same face was used for all photographs.…”
Section: Methodsmentioning
confidence: 99%
“…During the earliest consultation a patient will develop a first impression of the physician through a verbal and nonverbal communication. Professional presentation of a physician, proficiency and caring about confidentiality issues all contribute to create a right link between a physician and a patient (2,4). While the physician starts to build up trust, patient's impression is going to grow as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [ 12 15 ] have demonstrated that many providers do not have systems that can ensure that the test results are reliably communicated to patients. As shown in [ 16 , 17 ] normal and abnormal test results are commonly missed, even when a health care system widely uses electronic health records (EHRs), and providers miss 1–10% of abnormal test results.…”
Section: Introductionmentioning
confidence: 99%